Effects of power influence on the relationship between department store and its subtenants in China - Yip, Leslie Sai-chung (Curtin University, 2003)
The perspective that asymmetrical power relationship on vertical channel would lead to dominating partner exploitation with the use of coercive power is examined within the context of horizontal channel exchange relationship between department stores and tenant retailers. A power structure-action-outcome framework is offered to study casual links between dependence (structural aspects of power), use of coercive and noncoercive power (action), and three aspects of outcome - economic and social satisfaction, commitment and strategic performance. Data was collected through personal interview with 302 small, medium size retail tenants of department stores in PR China. Analysis of findings provided support to the model and the hypotheses. Results confirmed that dependence and use of power were only weakly related. The findings demonstrate the contextual influence of Chinese collectivistic culture on coercive power which involves the use of punishment or penalty. To further explore the relationship between dependence and power, investigation was carried out to examine if dependence moderates the effect of coercive power on economic satisfaction, with a positive result. On the other hand, use of non-coercive power showed positive results for economic and social satisfaction, which are positively related to commitment and strategic performance. It can be concluded that use of non-coercive power is strongly recommended for store-tenant relationship in the retail sector of China. Once again, the importance of channel context must not be ignored in the study of distribution channel issues.This research project contributes to the channel literature by adding to the contemporary state of knowledge on the use of power in horizontal channel relationships with power asymmetry, and constructs were brought together that have not been empirically investigated within a single study. It is unique in that the model was tested in non-American setting, namely PR China.